Peningkatan pengetahuan penggunaan antibiotik pada masyarakat sukadana melalui sosialisasi DAGUSIBU - Candra Eka Puspitasari; Nadya A. Turisia; Alfan Fauzi (Universitas Mataram, 2023)
Antibiotics are drugs used to treat infectious diseases caused by bacteria. Using antibiotics irrationally can cause antibiotic resistance. DAGUSIBU socialization aims to see the level of knowledge of villagers in Sukadana village regarding the use of antibiotics. This socialization was carried out by pharmacists followed by practice using the Cara Belajar Insan Aktif (CBIA) Method. The audience was dominated by women where the largest age range was 17-28 years old (65%). Respondent’s education was dominated by senior high school level or equivalent (70%). After the DAGUSIBU socialization, the community's knowledge about antibiotics has increased by 44%.